Skin Antisepsis Prior to Surgical Fixation of Open Extremity Fractures - Gouveia, Kyle (My University, 2024)
Open fractures are devastating injuries that lead to significant morbidity and prolonged disability to a large number of patients worldwide. In addition to bony union, the prevention of infection is a primary goal in the surgical treatment of open fractures, and is an important factor in determining a positive outcome. In addition to preoperative antibiotics and tetanus prophylaxis, along with surgical irrigation and debridement, perioperative skin antisepsis is part of the standard of care for these injuries. Despite recent randomized trials investigating different primary active ingredients in these skin antiseptic agents, it remains unclear whether alcohol-based skin antiseptics outperform aqueous solutions. This thesis comprises a combined analysis utilizing all open fracture participants from the PREP-IT trials, A-PREP and PREPARE. With these data, we were able to compare the risk of surgical site infection between alcohol-based and aqueous solutions, as well as examine specific subgroups including upper vs lower extremity open fractures as well as stratifying the fractures based on the severity of soft-tissue injury. The secondary outcome was to compare rates of unplanned reoperation up to 1-year following definitive fracture fixation. We demonstrated that for a large and diverse population of open fracture patients, the use of an alcohol-based or aqueous solution did not have a significant effect on the risk of surgical site infection following surgery for an open fracture. Moreover, we showed that there was also no significant difference in the risk of unplanned reoperation. These findings suggest that unlike in closed fractures as demonstrated by PREPARE, in open fractures the choice of surgical skin antiseptic agent has little impact on the risk of surgical site infection. This provides surgeons with the knowledge that either an alcohol-based or aqueous skin antiseptic solution can be used, and supports the use of iodine povacrylex in alcohol for all fractures given its proven effectiveness in the closed fracture population.